2009
DOI: 10.1002/elsc.200800038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetrahydrofuran on the binding of the competitive inhibitor proflavin and the storage stability of bovine pancreatic α‐chymotrypsin

Abstract: The binding of the competitive inhibitor proflavin by bovine pancreatic α‐chymotrypsin in water‐tetrahydrofuran mixtures was studied in the entire range of thermodynamic water activities at 25°C. The data on the binding of proflavin were compared with the results on the storage stability of α‐chymotrypsin in water‐organic mixtures. An analysis of the concentration dependency of these characteristics demonstrated that, at low water activity values, the interprotein contacts in the enzyme formed during its dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…172,177 In spite of the vast study of organic solvent effect on CT structure and stability, scattered literature exists of a set of water-soluble organic compounds such as acetonitrile 115,116,132,156,176,178−180 and teterahydrofuran. 115 CT is observed to be less active in acetonitrile, the most polar solvent in which the enzyme is most flexible. 156 Sasaki et al 180 observed that the structure and catalytic activity of CT in acetonitrile/water and tetrahydrofuran/water is dependent on the solvent composition similar to that observed in the case for ethanol/water mixtures.…”
Section: Influence Of Organic Solvents On the Stability And Structure...mentioning
confidence: 96%
See 2 more Smart Citations
“…172,177 In spite of the vast study of organic solvent effect on CT structure and stability, scattered literature exists of a set of water-soluble organic compounds such as acetonitrile 115,116,132,156,176,178−180 and teterahydrofuran. 115 CT is observed to be less active in acetonitrile, the most polar solvent in which the enzyme is most flexible. 156 Sasaki et al 180 observed that the structure and catalytic activity of CT in acetonitrile/water and tetrahydrofuran/water is dependent on the solvent composition similar to that observed in the case for ethanol/water mixtures.…”
Section: Influence Of Organic Solvents On the Stability And Structure...mentioning
confidence: 96%
“…113 This is accompanied by a large increase in catalytic activity 105 and in the internal flexibility of the enzyme. 108,114 In this regard, Sirotkin et al 115 proposed that at low water activities, water molecules penetrate into the structure of the enzyme, break interprotein contacts, and hydrate the polar groups of these contacts. At low water activities, interprotein contacts play a negative role, hindering the formation of the active form of the enzyme.…”
Section: Ct Activity In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Residual enzyme activity was determined by measuring the enzyme activity after storage in water–organic mixtures as described previously . The model process was the hydrolysis of N ‐acetyl‐ l ‐tyrosine ethyl ester (ATEE) catalyzed by α‐chymotrypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Residual enzyme activity was determined by measuring the enzyme activity after storage in water-organic mixtures as described previously. 31 The model process was the hydrolysis of N-acetyl-L-tyrosine The reaction mixture was prepared as follows. The dried or hydrated a-chymotrypsin was immersed in an aqueous-organic mixture of required composition, and was incubated at 258C for 60 min.…”
Section: Residual Enzyme Activitymentioning
confidence: 99%